Scrotal Swelling in a CAPD Patient: A Case of Suspected Dialysate Leak Presenting as Hydrocele - Riastana, I Made (Green Publisher, 2025)
Peritoneal dialysis, particularly Continuous Ambulatory Peritoneal Dialysis (CAPD), is an established modality for renal replacement therapy in patients with end-stage kidney disease (ESKD). Although generally safe, mechanical complications such as dialysate leakage can significantly disrupt treatment. Case Report: We present the case of a 32-year-old male with ESKD on dual dialysis (CAPD and hemodialysis) who developed acute right scrotal swelling following CAPD fluid exchange. Physical examination and imaging raised suspicion of a dialysate leak into the scrotal sac, potentially through a patent processus vaginalis, mimicking hydrocele. CAPD was suspended, and the patient was switched to hemodialysis while awaiting urological evaluation. Discussion: This case highlights the diagnostic challenge of differentiating dialysate leak from other causes of scrotal swelling, such as hydrocele, hernia, or infection. Prompt identification and management are essential to prevent further complications and maintain dialysis access. Conclusion: Dialysate leakage should be considered in CAPD patients presenting with acute scrotal swelling. Multidisciplinary evaluation and temporary suspension of peritoneal dialysis are often necessary for diagnosis and recovery.